Hepatoid adenocarcinoma of the stomach with ideal response to neoadjuvant chemo-immunotherapy: a case report - Li, Linchuan; Zhang, Dexu; Zhu, Jiankang; Zhang, Guangyong (Frontiers in Immunology, 2025)
Hepatoid adenocarcinoma of the stomach (HAS) is a rare subtype of gastric cancer characterized by histological features resembling hepatocellular carcinoma. Surgical intervention remains the preferred treatment modality for eligible patients. However, the efficacy of neoadjuvant therapy and alternative treatment regimens has been found to be suboptimal. Consequently, due to the high metastatic potential and unfavorable biological behavior of HAS, the prognosis for affected patients is exceedingly poor. We present a case involving a 64-year-old male diagnosed with advanced HAS, who demonstrated significant antitumor responses following a preoperative regimen of chemotherapy combined with immunotherapy, specifically utilizing oxaliplatin, S-1, and sintilimab. Over a 2-month period of neoadjuvant therapy, the patient’s serum α-fetoprotein level significantly decreased from 52,951.56 ng/mL to 241.04 ng/mL. Computed tomography scans revealed substantial tumor regression. Subsequent radical surgical intervention confirmed significant tumor shrinkage, with no evidence of lymph node metastasis upon pathological examination. This is the first report of chemotherapy combined with sintilimab in the treatment of gastric hepatoid adenocarcinoma, which may provide novel insights into the therapeutic strategy for HAS.